Flow cytometric measurement of intracellular Th1 and Th2 cytokine production by human villous and extravillous cytotrophoblast. - Sacks, G; Clover, L; Bainbridge, DR; Redman, C; Sargent, I (2001)
A wide variety of cytokines are present at the maternal-fetal interface, but the extreme cellular complexity of the placenta has made it difficult to determine which cytokines are produced by which cells. Hence novel flow cytometric methods have been applied to determine intracellular cytokine production by specific cell-types in placental cell suspensions. Cell suspensions were prepared from first and third trimester chorionic villi and third trimester amniochorion by enzymatic digestion and Percoll density gradient centrifugation. After overnight incubation in the presence of monensin, cells were fixed, permeabilized and labelled with antibodies for villous cytotrophoblast (cytokeratin+, MHC class I-), extravillous cytotrophoblast (cytokeratin+, MHC class 1+) and leucocytes (CD45+). These cell types were further characterized by their expression of EGFR (proliferative cytotrophoblast) and c-erbB2 (invasive cytotrophoblast). Production of IL-4, IL-10, TNF-alpha, IFN-gamma and IL-12 was determined by simultaneous labelling with the appropriate monoclonal antibodies. Only IL-4 was detected consistently in all samples of cytotrophoblast. IL-10 was not detected but IL-10 mRNA was demonstrated in third trimester chorionic villus digests by RT-PCR. Although IL-4 secretion has not been demonstrated, these data suggest that, in vivo there may be a "Th2 type cytokine bias" orchestrated by the trophoblast. It is proposed that other cytokines (including IL-10 and TNF-alpha) are produced by decidual leukocytes, and not cytotrophoblast, at the maternal-fetal interface.